Role Of Guduchi (Tinospora Cordifolia Miers.) in Autoimmune Disorders; A Review Article. - Sharma, Vijay Bhushan; Sharma, AAkanksha; Singh, Chandan (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is science of life with the aim of attaining health and curing disease of ill. Among thirteen types of Agni, Jatharagni is main and when it gets tone down, all other Agnis become diminished too. As a result of that phenomenon, Deha-dhatu remains in inchoate form, that vitiated the Adhya dhatu Rasa when this vitiated Rasa enters in Amasaya, it is called as Ama (an unripe form of Rasa). Autoimmunity is the condition when the immune system produces a response against one or more of the body’s normal constituents as if they are harmful. The response may include specific immune cells and/or antibodies. In ancient Ayurvedic text a disease Amavata is said to be caused by Ama. In modern perspective Amavata can be correlated with Rheumatoid arthritis, which is an autoimmune disorder. So here Ama can be correlated with free radicals present in the body and blood. Guduchi (Giloy) comprises proven scientific effects over the oxidative stress in the body as it comprises antioxidants and qualities to rejuvenate the body hence called Amrita and Rasayana. It has Deepana, Amahara, Rasayana, Sangrahi and Vayasthapana properties, that’s why it is useful in Pachana of Ama and hence management of Autoimmune disorders caused by Ama.